Domestic antidotes to sudden stops - Eduardo A. Cavallo; Alejandro Izquierdo; John J. León-Díaz (Inter-American Development Bank (IDB), 2017)
Sudden Stops in net capital flows can be prevented when the actions of domestic investors offset a reduction in foreign lending. This paper presents evidence that while sudden stops in gross inflows-i.e., a tightening of the external borrowing constraint-are associated with global conditions and therefore, are largely outside of the control of local policymakers, domestic factors such as low levels of liability dollarization, exchange rate flexibility, inflation targeting regimes, and a solid institutional background are important to prevent these episodes from becoming sudden stops in net capital flows. Under these favorable local conditions, domestic investors may perceive reduced risk in bringing in resources at the time of an external shock, thus insulating the country from this shock.
Keywords: F30; F32; F40; 330; Gross capital flows; Sudden stops; Retrenchments; Domestic versus foreign investors